The Effect Of Online Presentation Using Zoom On Students’ Public Speaking Skills - Srinawati, Wawat; Kurnia, Hanifah; Rahmayanti, Rahmayanti; Nia, Nia; Salsabila, Nada Fat-hia; Afinashafa, Vico Farez (DAS CONFERENCE INTERNATIONAL SERIES, 2026)
This study aims to examine the effect of online presentations using Zoom on the public speaking skills of third-semester students of the English Education Department. The study employed a quantitative approach using a quasi-experimental research design. Zoom was utilized as the main platform for online presentations, incorporating features such as video conferencing, screen sharing, and live interaction. The development of digital communication technology has significantly influenced teaching and learning practices in higher education, particularly in improving students’ public speaking skills. Online presentation platforms such as Zoom are increasingly used as learning media in speaking courses. However, the effectiveness of online presentations using Zoom in enhancing students’ public speaking skills still needs to be investigated. The participants of this study were third-semester students who had similar academic backgrounds and learning conditions. The results show that online presentations using Zoom have a positive effect on students’ public speaking skills, particularly in terms of confidence, fluency, pronunciation, and audience engagement. These results indicate that the findings are consistent with the use of technology-supported learning in developing speaking performance. In conclusion, online presentations using Zoom can effectively improve students’ public speaking skills. Therefore, it is recommended that lecturers integrate Zoom-based online presentations as part of instructional strategies in public speaking courses.